2018
DOI: 10.2147/ijn.s152163
|View full text |Cite
|
Sign up to set email alerts
|

A hydrogel biosensor for high selective and sensitive detection of amyloid-beta oligomers

Abstract: Background Alzheimer’s disease (AD) is a neurodegenerative disorder characterized by progressive cognitive and memory impairment. It is the most common neurological disease that causes dementia. Soluble amyloid-beta oligomers (AβO) in blood or cerebrospinal fluid (CSF) are the pathogenic biomarker correlated with AD. Methods A simple electrochemical biosensor using graphene oxide/gold nanoparticles (GNPs) hydrogel electrode was developed in this study. Thiolated cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…Aβ oligomers, playing a key-role in AD pathogenesis, have become a promising candidate for AD diagnosis. Efforts to measure Aβ oligomers in humoral fluids are currently underway (5)(6)(7). However, cost-effective and non-invasive diagnostic methods to detect Aβ oligomers are not currently available in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aβ oligomers, playing a key-role in AD pathogenesis, have become a promising candidate for AD diagnosis. Efforts to measure Aβ oligomers in humoral fluids are currently underway (5)(6)(7). However, cost-effective and non-invasive diagnostic methods to detect Aβ oligomers are not currently available in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…no abnormality on the Health Screening Questionnaire(18);(3) absence of memory complaints; (4) a Korean Dementia Screening Questionnaire score ≤ 6 (19);(5) normal general cognition (within 1 standard deviation of the age-and education-adjusted norms of the Korean version of the Mini-Mental State Examination (20) and a score > 26); (6) intact activities of daily living (K-IADL ≤ 0.42); (7) no depression (the short-form Geriatric Depression Scale ≤ 7); (8) no history of thyroid dysfunction, vitamin B12 deficiency, or folate deficiency; (9) No abnormalities on the MRI scan. A more stringent inclusion criteria was applied to patients with AD dementia (ADD): (1) the probable AD criteria proposed by the National Institute of Neurological and Communicative Disorders and Stroke and the Alzheimer's Disease and Related Disorders Association (NINCDS-ADRDA) (21), as well as the DSM-IV; (2) a follow-up of at least 6 months to determine the clinical course of AD by experienced neurologists; (3) male or female patients between the ages of 50 to 80, (4) education for at least 6 years.…”
mentioning
confidence: 99%
“…Research into Alzheimer's disease has found that oligomerized Aβ (OAβ) are the most toxic among Aβ species [6,7] and are highly associated with the pathogenesis of AD [8,9]. Various efforts are being made to detect oligomerized Aβ in biofluid [10,11] with the aim of validating it as the long-anticipated blood-based biomarker for AD diagnosis. Multimer Detection System-Oligomeric Amyloid-β (MDS-OAβ) [12] is a technique which measures the level of the Aβ oligomerization (AβO) tendency after spiking purified synthetic Aβ into plasma samples.…”
Section: Introductionmentioning
confidence: 99%
“…2, relationships between the beam tip deflection and the applied voltage based on Eqs. (13) and 17is shown. As it can be seen, the electrode deflection gradually increases by applying potential difference.…”
Section: Parametric Studymentioning
confidence: 98%
“…Biosensors have been introduced to detect different characteristics of biological particles. They have numerous applications in biotechnology as biomass detectors 1,2 , thermal switches [3][4][5][6] , smart resonators [7][8][9][10][11][12] , and other biomedical devices [13][14][15][16][17][18][19][20][21][22][23][24] . Due to the important biological applications of such systems in the drug delivery, clinical diagnostics, measurement, and organism detection, many scientists have studied their features such as operational range, instability, and performance 8,24,25 .…”
mentioning
confidence: 99%